1999
DOI: 10.1001/archpedi.153.5.446
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Passive Smoking, Race, and Coronary Artery Disease Risk

Abstract: Background: Children with long-term exposure to passive cigarette smoke may be at elevated risk for the development of premature coronary artery disease (CAD). Objective: To examine how CAD risk factors, exposure to passive smoking, sex, and race are related in pubertal children and to determine if there is an identifiable childhood risk profile (ie, does passive smoking interact with other coronary risk factors to increase the risk of developing premature CAD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 31 publications
2
25
1
Order By: Relevance
“…78 HDL 2 , the antiatherogenic subfraction of HDL, is decreased by SHS exposure. 78,79 Women exposed at work to SHS for 6 h/d for at least the past 6 consecutive months had HDL 2 levels significantly lower than those of unexposed women. The decrease in passive smoking women was similar to the decrease in smokers (31% and 33% HDL 2 percentage decrease from the levels in unexposed, respectively).…”
Section: Effects On Hdlmentioning
confidence: 97%
See 1 more Smart Citation
“…78 HDL 2 , the antiatherogenic subfraction of HDL, is decreased by SHS exposure. 78,79 Women exposed at work to SHS for 6 h/d for at least the past 6 consecutive months had HDL 2 levels significantly lower than those of unexposed women. The decrease in passive smoking women was similar to the decrease in smokers (31% and 33% HDL 2 percentage decrease from the levels in unexposed, respectively).…”
Section: Effects On Hdlmentioning
confidence: 97%
“…73 Racial and gender differences have been noted in the effects of SHS on lipid metabolism in children; data from cohorts of white and black twin children have shown an interaction between race and gender. 79 In children exposed to SHS, HDL levels were lower in whites than in blacks (43.2Ϯ8.0 [meanϮSD] versus 52.7Ϯ8.4 mg/dL, respectively). These data suggest that white males exposed to passive smoking may be more susceptible to the effects of SHS than blacks or females.…”
Section: Effects On Hdlmentioning
confidence: 99%
“…16,17 In adults, heavy workplace exposure to tobacco smoke has been demonstrated to have an adverse influence on serum lipids. 18,19 Recently, it was indicated that maternal smoking in pregnancy is associ- 21 Exposure to tobacco smoke as indicated by objective measurement, serum cotinine concentration, has been frequently determined in school-aged children.…”
mentioning
confidence: 99%
“…Only about one third (35%) of parents prohibited smoking inside the home and only 22% prohibited smoking in cars [88]. Parents need to be aware that ETS is classified by the US Environmental Protection Agency as a class A carcinogen [4] and that exposing their children to ETS increases the risk of asthma, sudden infant death syndrome, middle ear disease, pneumonia, cough, upper respiratory infection, reduced high-density lipoprotein levels, and coronary artery disease [8,[89][90][91][92][93][94][95].…”
Section: Discussionmentioning
confidence: 99%